2012
DOI: 10.1055/s-0032-1323747
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise Enhances Cognitive Function in Mouse

Abstract: Physical exercise has been shown to increase adult neurogenesis in the hippocampus and to enhance synaptic plasticity. It has been demonstrated that these neuroprotective effects can be observed following aerobic exercise. However, it remains unknown whether plasticity molecules, such as brain-derived neurotrophic factor (BDNF) and cyclic AMP response element-binding protein (CREB), are expressed in the hippocampus following resistance exercise. We applied voluntary progressive-resistance wheel exercise (RE) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
0
23
1
1
Order By: Relevance
“…The demonstrated improvements in learning and memory correlated with a 2-fold increase in neurogenesis in the hippocampus of PA mice (Gibbons et al, 2014). Several other studies presented similar results, demonstrating elevated brain concentrations of BDNF, VEGF and IGF-1, a decrease in ROS and increased learning and memory with the introduction of PA and exercise (Erickson et al, 2012;Eyre and Baune, 2012;Radak et al, 2007;Radak et al, 2013;Suijo et al, 2013;Yu et al, 2014). PA and exercise have also been shown to improve memory in mouse models of AD, and it has been suggested that this improvement may be attributed to the PA-induced decline in neuroinflammation (Kang et al, 2013;Tapia-Rojas et al, 2016;Zhao et al, 2015).…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 61%
See 1 more Smart Citation
“…The demonstrated improvements in learning and memory correlated with a 2-fold increase in neurogenesis in the hippocampus of PA mice (Gibbons et al, 2014). Several other studies presented similar results, demonstrating elevated brain concentrations of BDNF, VEGF and IGF-1, a decrease in ROS and increased learning and memory with the introduction of PA and exercise (Erickson et al, 2012;Eyre and Baune, 2012;Radak et al, 2007;Radak et al, 2013;Suijo et al, 2013;Yu et al, 2014). PA and exercise have also been shown to improve memory in mouse models of AD, and it has been suggested that this improvement may be attributed to the PA-induced decline in neuroinflammation (Kang et al, 2013;Tapia-Rojas et al, 2016;Zhao et al, 2015).…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 61%
“…Experimental and epidemiological studies have demonstrated that living a healthy and physically active lifestyle reduces the risk (Barnes and Yaffe, 2011;Scarmeas et al, 2009;Zou et al, 2015) and severity of neurological diseases (Archer and Kostrzewa, 2015;Canning et al, 2015;Erickson et al, 2012;Eyre and Baune, 2012;Frazzitta et al, 2015;Frazzitta et al, 2014;Liu et al, 2013;Radak et al, 2007;Radak et al, 2013;Suijo et al, 2013;Uc et al, 2014;Yu et al, 2014). However, the cellular and molecular mechanisms responsible for these beneficial effects of PA have not been established.…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…Much of this is likely due to the realization of benefits of resistance training that is now recommended for the prevention and rehabilitation of disease and musculoskeletal injury [1,2,3,4,5]. Resistance exercise is known to have positive health effects on numerous tissues including heart [6], bone [7], skeletal muscle [8] and corticospinal [9] as well as hippocampal [10] nervous tissue.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Exercised animals show an enhanced performance in spatial learning and memory tasks such as the Morris water maze and radial arm water maze (Khabour et al, 2013; Suijo et al, 2013). Exercise can also modify non-spatial learning and memory as shown in passive avoidance and object recognition (Bechara and Kelly, 2013; Hosseini et al, 2013; Radahmadi et al, 2013; Souza et al, 2013).…”
Section: Introductionmentioning
confidence: 99%